2018
DOI: 10.1002/jcp.26537
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 fatty acids modulate the lipid profile, membrane architecture, and gene expression of leiomyoma cells

Abstract: Uterine leiomyomas (fibroids or myomas) are the most common benign tumors of premenopausal women and new medical treatments are needed. This study aimed to determine the effects of omega-3 fatty acids on the lipid profile, membrane architecture and gene expression patterns of extracellular matrix components (collagen1A1, fibronectin, versican, or activin A), mechanical signaling (integrin β1, FAK, and AKAP13), sterol regulatory molecules (ABCG1, ABCA1, CAV1, and SREBF2), and mitochondrial enzyme (CYP11A1) in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
2
7
1
Order By: Relevance
“…In fact, ulipristal acetate and omega-3-fatty acids downregulate AKAP13 expression in uterine leiomyoma. 11,28 In this study, we also found that simvastatin decreases AKAP13 expression in leiomyoma cells.…”
Section: Results Of the Study In The Context Of What Is Knownsupporting
confidence: 70%
“…In fact, ulipristal acetate and omega-3-fatty acids downregulate AKAP13 expression in uterine leiomyoma. 11,28 In this study, we also found that simvastatin decreases AKAP13 expression in leiomyoma cells.…”
Section: Results Of the Study In The Context Of What Is Knownsupporting
confidence: 70%
“…In contrast, linoleic acid metabolism undergoes changes only in UF cells. Differences in the metabolism of linoleic acid in UF cells compared with myometrial cells, as well as a changes in the fatty acid profile of the cells were previously noted by Islam and Castellucci 61 .
Figure 2 Diagram of metabolic pathways for lipid species with statistically significant abundance variation common for benign tumor and myometrium during recurrence of fibroids.
…”
Section: Resultssupporting
confidence: 60%
“…It also reduced cytochrome 450 family member-CYP11A1, the mitochondrial enzyme that catalyzes the conversion of cholesterol to pregnenolone. Authors concluded that omega-3 fatty acids modulate lipid profile, mechanical signaling, and cellular lipid accumulation in UFs [177]. Pregnenolone is a precursor for biosynthesis of many steroid hormones including progestogens, which is an important hormone in UF biology.…”
Section: Anthocyaninsmentioning
confidence: 99%